KCC2 mediates NH4+ uptake in cultured rat brain neurons - Liu, Xiuxin; Titz, Stefan; Lewen, Andrea; Misgeld, Ulrich (Journal of neurophysiology and neurological disorders, 2003)
Elevated levels of in the brain impair neuronal function. We studied the effects of on postsynaptic inhibition of cultured rat brain neurons using whole cell recording under nominally -free conditions. Application of shifted the reversal potentials for spontaneous inhibitory postsynaptic currents and currents elicited by dendritic GABA applications in a positive direction because [Cl-]i increased. The positive shift of the reversal potentials of GABA-induced Cl- currents was equal on equimolar elevation of or [K+]o, respectively. The -induced increase in [Cl-]i was reversed by an inhibitor of cation-anion cotransport, furosemide (0.1 mM), but not by bumetanide (0.01 mM) or by replacement of [Na+]o by Li+. We conclude that neuron-specific K-Cl cotransporter (KCC2) transports similar to K+. Despite this fact, the small increase of during metabolic encephalopathies will barely elevate [Cl-]i. However, an impairment of neuronal function may result because KCC2 provides a pathway to accumulate , and thereby, a continuous acid load to neurons.
Im Titel ist "4" tiefgestellt und "+" hochgestellt
Gesehen am 08.04.2021